Strategi Guru dalam Meningkatkan Kemampuan Membaca Siswa SD melalui Cerita Rakyat Nusantara - Thalita Fitra Amaliya; Nurul Husna Zakiyah; Restia Amelia; Afriza Media; Ari Suriani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to examine how elementary school teachers enhance students’ reading skills using Indonesian folklore as a learning medium. The study employed a qualitative descriptive approach, with data gathered through classroom observations, teacher interviews, and analysis of instructional materials. The results indicate that teachers apply various contextual teaching strategies, including guided reading, storytelling, group discussions, and vocabulary development using folklore texts. These methods help foster student engagement and improve reading comprehension. The study highlights the importance of integrating local cultural content into literacy instruction at the primary education level.